Crosslinked cellulose-based dry water-absorbing fabric and preparation method and application thereof

CN119465616BActive Publication Date: 2026-10-16SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411529205.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2026-10-16
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

[0008]目前,对醚化纤维素应用有很多,但由于醚化程度在工业化流程中不可控,导致无法稳定地大批量地生成均匀的醚化纤维素

Benefits of technology

本发明通过微波辅助醚化,解决了纤维素醚化不均匀、反应时间长、的问题;利用柠檬酸进行交联处理,增加水凝胶纤维敷料的分子间作用力,解决纤维素基布力学性能差和保液率低的问题。此外,本发明制备工艺简单、性能可控、易于规模化加工,本发明的干态吸水织物在快速吸收液体后能够形成具有良好保液能力、力学性能、透明度的纤维状水凝胶,可应用于各类创面修复场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465616B_ABST
    Figure CN119465616B_ABST
Patent Text Reader

Abstract

The application belongs to the field of medical materials, and discloses a crosslinked cellulose-based dry-state water-absorbing fabric and a preparation method and application thereof. The preparation method comprises the following steps: soaking a cellulose-based fabric in a potassium chloride solution; controlling the water content of the cellulose-based fabric after washing by using a mangle; performing alkali treatment on the fabric; performing etherification treatment on the fabric by using a microwave-assisted technology; performing crosslinking on the fabric; and obtaining the crosslinked cellulose-based dry-state water-absorbing fabric after drying. The crosslinking treatment significantly improves the mechanical properties and liquid retention rate of the cellulose-based hydrogel fiber. The preparation process of the crosslinked cellulose-based dry-state water-absorbing fabric is simple, controllable, and easy to realize large-scale production. After absorbing liquid, the crosslinked cellulose-based dry-state water-absorbing fabric can quickly form a fibrous hydrogel with good liquid retention capacity, mechanical properties and transparency, and is suitable for various wound repair scenarios, and has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Background Technology

[0001] As the body's first line of defense against physical damage and microbial invasion, the skin is indispensable for ensuring human safety and maintaining life. Intact skin is the body's first line of defense against the external environment and microorganisms, making it one of the most vulnerable organs. Every year, millions of people suffer skin injuries due to various physical and chemical factors or diseases. Traditional dry wound dressings, such as gauze, bandages, and absorbent cotton, while protecting wounds and absorbing some exudate, still have many drawbacks that hinder wound healing, such as easy adhesion to the wound, secondary damage during dressing changes, and inability to prevent infection. With societal progress and advancements in medical technology, traditional dressings no longer meet the needs of modern wound treatment for complex or chronic wounds, making novel wound dressings a focus of research.

[0002] Studies have shown that a moist environment promotes cell adhesion, proliferation, and differentiation, thus helping to prevent wound infection. Hydrogels, with their unique moisturizing properties and biocompatibility, have become ideal materials for wound dressings. Early hydrogel dressings were primarily used to absorb wound exudate and provide basic physical protection. Wound healing is a complex process, broadly divided into four stages: hemostasis, inflammation, proliferation, and tissue remodeling. With a deeper understanding of these processes, hydrogel dressings have begun to integrate more bioactive ingredients, such as growth factors and antibacterial agents. Modern hydrogel dressings not only promote wound healing but also possess intelligent responsiveness, adjusting drug release according to changes in the wound environment.

[0003] With innovation in materials science and increasing public emphasis on sustainable development, hydrogel dressings are showing a significant trend towards diversification in material selection. In addition to traditional synthetic polymers, naturally derived polymers are also being extensively studied due to their inherent good biocompatibility. Furthermore, semi-synthetic polymers, including carboxymethyl cellulose, have also attracted attention due to their good biocompatibility and liquid absorption properties.

[0004] Hydrogel fibers, a combination of fabric and hydrogel, can overcome some of the shortcomings of traditional dressings when used in wound dressings. Their fibrous nature provides a high specific surface area and high breathability, facilitating more effective gas exchange and reducing the moist environment around the wound and the risk of infection. Simultaneously, their hydrogel properties allow them to maintain high water content, helping to maintain the moisture balance of the skin wound surface. Furthermore, the highly elastic hydrogel wound dressings can adapt to wounds of different shapes and are less prone to breakage during use. Therefore, hydrogel fibers, combining the advantages of hydrogel and fiber materials, are well-suited for applications in wound dressings.

[0005] With innovation in materials science and increasing public awareness of sustainable development, hydrogel dressings are showing a significant trend towards diversification in material selection. They can be broadly categorized into three types: traditional synthetic polymers, naturally derived polymers, and semi-synthetic polymers. Regardless of the material chosen, its absorbency, water retention, and biocompatibility must be considered when applying it to wound dressings.

[0006] Carboxymethyl cellulose (CMC) possesses numerous advantages, including abundant supply, low cost, ease of functionalization, and good biocompatibility. Its biocompatibility, biodegradability, bioadhesion, and tissue similarity are particularly noteworthy, making it a focus of research in wound dressings. Gel formation of CMC maintains a moist environment around the wound and increases blood viscosity, thereby improving hemostasis. Currently, CMC gelation can be achieved through etherification. Etherification significantly alters the solubility of cellulose, increasing its solubility in water. This solubility variation is related to the degree of substitution, the size of the substituents, and the polarity of the substituents. However, in wound dressings, excessively etherified cellulose may fail to maintain its basic morphology in aqueous solutions, or even cause some of the etherified cellulose to adhere to the wound site, which is detrimental to wound healing.

[0007] Etherified cellulose hydrogels exhibit a significant decrease in mechanical properties after absorbing water, which is undesirable in wound dressings. Crosslinking is a commonly used method to enhance the mechanical properties of hydrogels, and moderate crosslinking can also help maintain the hydrogel's morphology after water absorption, which is beneficial for its application in wound dressings.

[0008] Currently, etherified cellulose has many applications, but the degree of etherification is uncontrollable in industrial processes, making it impossible to stably produce uniform etherified cellulose in large quantities. Furthermore, the cellulose produced by current etherification methods either has unstable shape and low mechanical properties, or insufficient water absorption, failing to adequately meet the requirements for wound dressing applications. Summary of the Invention

[0009] In order to overcome the shortcomings and deficiencies of the prior art, the primary objective of this invention is to provide a method for preparing cross-linked cellulose-based dry absorbent fabric.

[0010] The present invention has a simple preparation process, short preparation cycle, controllable performance, easy large-scale processing and low cost; the dry absorbent fabric of the present invention can form a fibrous hydrogel with good liquid retention capacity, mechanical properties and transparency after rapidly absorbing liquid, and can be applied to various wound repair scenarios.

[0011] Another object of the present invention is to provide a cross-linked cellulose-based dry absorbent fabric prepared by the above method.

[0012] Another object of the present invention is to provide the application of the above-mentioned cross-linked cellulose-based dry absorbent fabric in wound dressing materials.

[0013] The objective of this invention is achieved through the following solution: A method for preparing a cross-linked cellulose-based dry absorbent fabric includes the following steps: (1) The base fabric is soaked in potassium chloride solution, heated, washed, and rolled until the water content is 50wt%-90wt% to obtain sample a; (2) Immerse sample a in sodium hydroxide solution and react to obtain alkalized sample b; (3) Add etherification solution to alkalized sample b, react under microwave assistance, wash, and obtain etherified sample c; (4) Immerse the etherified sample c in the crosslinking agent solution and react. The resulting product is washed and dried to obtain a crosslinked cellulose-based dry absorbent fabric.

[0014] The base fabric in step (1) comprises 60%-100% cellulose fiber and 0%-40% non-cellulose fiber by weight percentage.

[0015] The cellulose fiber includes at least one of Tencel cellulose, viscose fiber, modal fiber, cotton fiber, cupro fiber, linen fiber, and acetate fiber; the non-cellulose fiber is an alkali-resistant non-cellulose fiber, including at least one of nylon fiber, vinylon fiber, and polypropylene fiber.

[0016] The base fabric in step (1) is at least one of spunlace nonwoven fabric, needle-punched nonwoven fabric, sewn nonwoven fabric, knitted fabric, and woven fabric.

[0017] The concentration of the potassium chloride solution in step (1) is 20 wt%.

[0018] The mass ratio of the base fabric to the potassium chloride solution in step (1) is 1:5-15.

[0019] The heating treatment in step (1) is performed at a temperature of 50°C for 1 hour.

[0020] The pressure of the rolling mill in step (1) is 0.5 MPa.

[0021] In step (2), the mass ratio of sodium hydroxide to water in the sodium hydroxide solution is 1-10:50.

[0022] The mass ratio of the sodium hydroxide solution in step (2) to the base fabric in step (1) is 4-16:1.

[0023] The reaction in step (2) is carried out at a temperature of 25-60℃ for 30-180 min.

[0024] The solute in the etherification solution in step (3) is at least one of ethylene oxide, chloroacetic acid, propylene oxide, and chloromethane; the solvent is at least one of water and ethanol; and the mass ratio of solute to solvent is 1-5:20.

[0025] The mass ratio of the etherification solution in step (3) to the base fabric in step (1) is 3-10:1.

[0026] The microwave-assisted power in step (3) is 100-300 W; the reaction temperature is 40-70 ℃; and the time is 2-10 min.

[0027] The solute in the crosslinking agent solution in step (4) is at least one of citric acid, ethylene glycol diglycidyl ether, epichlorohydrin, tartaric acid, and genipin; the solvent is water; and the content of the solute in the crosslinking agent solution is 10-40 wt%.

[0028] The mass ratio of the crosslinking agent solution in step (4) to the base fabric in step (1) is 1-10:1.

[0029] The reaction in step (4) is carried out at a temperature of 70-110 °C for 30-120 min.

[0030] The drying process described in step (4) is either oven drying or freeze drying.

[0031] The cross-linked cellulose-based dry absorbent fabric prepared by the above method.

[0032] Application of the above-mentioned cross-linked cellulose-based dry absorbent fabric in wound dressing materials.

[0033] The specific application is as follows: the cross-linked cellulose-based dry absorbent fabric is placed in water to reach water absorption equilibrium, thereby obtaining cross-linked cellulose-based hydrogel fiber; the cross-linked cellulose-based hydrogel fiber is used as a wound dressing.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects: This invention solves the problems of uneven cellulose etherification and long reaction time by using microwave-assisted etherification; it also utilizes citric acid for cross-linking treatment to increase the intermolecular forces of the hydrogel fiber dressing, thus addressing the issues of poor mechanical properties and low liquid retention of cellulose-based fabrics. Furthermore, the preparation process of this invention is simple, the performance is controllable, and it is easy to scale up. The dry absorbent fabric of this invention can form a fibrous hydrogel with good liquid retention capacity, mechanical properties, and transparency after rapid liquid absorption, making it applicable to various wound repair scenarios. Attached Figure Description

[0035] Figure 1 This is a flowchart illustrating the preparation method of cross-linked cellulose-based dry absorbent fabric according to an embodiment of the present invention. Detailed Implementation

[0036] The present invention will be further described in detail below with reference to embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.

[0037] Unless otherwise specified, all reagents used in the examples are commercially available.

[0038] The tensile properties test methods for the products obtained in Examples 1-12 and Comparative Examples 1-2 refer to Part 1 of GB / T 3923.1-2013 "Textiles - Tensile Properties of Fabrics": Determination of breaking strength and elongation at break (strip method).

[0039] Comparative Example 1 Untreated spunlace nonwoven fabric (100wt% Tencel fiber) was used as a comparative example.

[0040] Performance testing: The dry fabric breaking strength of the product obtained in this example is 160 N; the water absorption ratio is 7 times.

[0041] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 80 N; after centrifugation at 1000 rpm for 5 min, it could retain 2 times the mass of the dry cloth in water; the skin contact time was 20 minutes; and it was opaque.

[0042] Comparative Example 2 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% using a rolling mill (pressure 0.5 MPa). Step 3: Immerse the above sample in 1000 g sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and react at 40 °C for 50 minutes to obtain the alkalized sample; Step 4: Add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed at a mass ratio of 1:9) to the alkalized sample, and react with microwave power of 230 W at 55 °C for 5 minutes to obtain the etherified sample. Step 5: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0043] Performance testing: The dry fabric breaking strength of the product obtained in this example is 74 N; the water absorption ratio is 16 times.

[0044] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 41 N; after centrifugation at 1000 rpm for 5 min, it could retain 10 times the mass of the dry cloth in water; the skin contact time was 160 minutes; and the transparency at 600 nm was 93%.

[0045] Example 1 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% by rolling (pressure 0.5 MPa); Step 3: Immerse the above sample in 1000 g sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and react at 40 °C for 50 minutes to obtain the alkalized sample; Step 4: Add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed at a mass ratio of 1:9) to the alkalized sample, and react with microwave power of 230 W at 55 °C for 5 minutes. Wash the product with water to obtain the etherified sample. Step 5: Add 100 g of 20 wt.% citric acid / water solution to the etherified sample, and seal the sample and place it at 80°C for 60 minutes. Step 6: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0046] Performance testing: The dry fabric breaking strength of the product obtained in this example is 90 N; the water absorption ratio is 23 times.

[0047] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 48 N; after centrifugation at 1000 rpm for 5 min, it could retain 13 times the mass of the dry cloth in water; the skin contact time was 240 minutes; and the transparency at 600 nm was 93%.

[0048] Example 2 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% by rolling (pressure 0.5 MPa); Step 3: Immerse the above sample in 1000 g sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:19, and react at 40 °C for 50 minutes to obtain the alkalized sample; Step 4: Add 500 g of ethylene oxide solution (ethylene oxide and ethanol are mixed at a mass ratio of 1:20) to the alkalized sample, and react with microwave power of 230 W at 55 °C for 5 minutes. Wash the product with water to obtain the etherified sample. Step 5: Add 100 g of 20 wt.% citric acid / water solution to the etherified sample, and seal the sample and place it at 95 °C for 60 minutes. Step 6: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0049] Performance testing: The dry fabric breaking strength of the product obtained in this example is 110 N; the water absorption ratio is 17 times.

[0050] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 60 N; after centrifugation at 1000 rpm for 5 min, it could retain 12 times the mass of the dry cloth in water; the skin adhesion time was 210 minutes; and the transparency at 600 nm was 95%.

[0051] Example 3 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% by rolling (pressure 0.5 MPa); Step 3: Immerse the above sample in 1000 g sodium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and react at 40 ℃ for 50 minutes to obtain the alkalized sample; Step 4: Add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed at a mass ratio of 1:9) to the alkalized sample, and react with microwave power of 230 W at 65 °C for 5 minutes. Wash the product with water to obtain the etherified sample. Step 5: Add 100 g of 20 wt.% citric acid / water solution to the etherified sample, and seal the sample and place it at 80 °C for 60 minutes. Step 6: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0052] Performance testing: The dry fabric breaking strength of the product obtained in this example is 87 N; the water absorption ratio is 29 times.

[0053] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 47 N; after centrifugation at 1000 rpm for 5 min, it could retain 15 times the mass of the dry cloth in water; the skin adhesion time was 260 minutes; and the transparency at 600 nm was 96%.

[0054] Example 4 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% by rolling (pressure 0.5 MPa); Step 3: Immerse the above sample in 1000 g sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and react at 50 °C for 30 minutes to obtain the alkalized sample; Step 4: Add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed at a mass ratio of 1:9) to the alkalized sample, and react with microwave power of 230 W at 55 °C for 5 minutes. Wash the product with water to obtain the etherified sample. Step 5: Add 100 g of 40 wt.% citric acid / water solution to the etherified sample, and seal the sample and place it at 80 °C for 60 minutes. Step 6: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0055] Performance testing: The dry fabric breaking strength of the product obtained in this example is 100 N; the water absorption ratio is 20 times.

[0056] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 53 N; after centrifugation at 1000 rpm for 5 min, it could retain 14 times the mass of the dry cloth in water; the skin adhesion time was 270 minutes; and the transparency at 600 nm was 94%.

[0057] Example 5 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% by rolling (pressure 0.5 MPa); Step 3: Immerse the above sample in 1000 g sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and react at 50 °C for 30 minutes to obtain the alkalized sample; Step 4: Add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed at a mass ratio of 1:9) to the alkalized sample, and react with microwave power of 230 W at 55 °C for 5 minutes. Wash the product with water to obtain the etherified sample. Step 5: Add 100 g of 20 wt.% citric acid / water solution to the etherified sample, and seal the sample and place it at 70 °C for 30 minutes. Step 6: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0058] Performance testing: The dry fabric breaking strength of the product obtained in this example is 82 N; the water absorption ratio is 28 times.

[0059] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 45 N; after centrifugation at 1000 rpm for 5 min, it could retain 15 times the mass of the dry cloth in water; the skin adhesion time was 230 minutes; and the transparency at 600 nm was 95%.

[0060] Example 6 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% by rolling (pressure 0.5 MPa); Step 3: Immerse the above sample in 400 g sodium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and react at 40 °C for 50 minutes to obtain the alkalized sample; Step 4: Add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed at a mass ratio of 1:9) to the alkalized sample, and react with microwave power of 100 W at 70 °C for 3 minutes. Wash the product with water to obtain the etherified sample. Step 5: Add 100 g of 20 wt.% citric acid / water solution to the etherified sample, and seal the sample and place it at 80°C for 60 minutes. Step 6: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0061] Performance testing: The dry fabric breaking strength of the product obtained in this example is 83 N; the water absorption ratio is 29 times.

[0062] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 46 N; after centrifugation at 1000 rpm for 5 min, it could retain 15 times the mass of the dry cloth in water; the skin adhesion time was 250 minutes; and the transparency at 600 nm was 96%.

[0063] Example 7 Step 1: Soak 100g of spunlace nonwoven fabric (100wt% Tencel fiber) as the base fabric in 1000g of 20wt.% potassium chloride solution, ensuring that the base fabric is completely wetted, and treat it at 50℃ for 1 hour to obtain the treated sample; Step two: Wash the treated sample with water, and control the sample moisture content to 50 wt% by rolling (pressure 0.5 MPa); Step 3: Immerse the above sample in 1000 g sodium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and react at 25 °C for 180 minutes to obtain the alkalized sample; Step 4: Add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed at a mass ratio of 1:9) to the alkalized sample, and react with microwave power of 230 W at 55 °C for 5 minutes. Wash the product with water to obtain the etherified sample. Step 5: Add 100 g of 20 wt.% citric acid / water solution to the etherified sample, and seal the sample and place it at 80°C for 60 minutes. Step 6: Wash the above sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0064] Performance testing: The dry fabric breaking strength of the product obtained in this example is 120 N; the water absorption ratio is 15 times.

[0065] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 65 N; after centrifugation at 1000 rpm for 5 min, it could retain 10 times the mass of the dry cloth in water; the skin contact time was 200 minutes; and the transparency at 600 nm was 90%.

[0066] Example 8 The difference between this embodiment and Embodiment 1 is that spunlace nonwoven fabric (100wt% viscose fiber) is used as the raw material.

[0067] Performance testing: Dry cloth tensile strength 85 N; wet cloth tensile strength 46 N; water absorption ratio 29 times; retains 15 times the amount of water after centrifugation at 1000 rpm for 5 min; skin contact time 280 minutes; transparency at 600 nm 94%.

[0068] Example 9 The difference between this embodiment and Embodiment 1 is that spunlace nonwoven fabric (100wt% modal fiber) is used as the raw material.

[0069] Performance testing: The dry fabric breaking strength of the product obtained in this example is 100 N; the water absorption ratio is 20 times.

[0070] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 54 N; after centrifugation at 1000 rpm for 5 min, it could retain 12 times the mass of the dry cloth in water; the skin adhesion time was 240 minutes; and the transparency at 600 nm was 92%.

[0071] Example 10 The difference between this embodiment and Embodiment 1 is that 20 wt.% ethylene glycol diglycidyl ether / water solution is used as the crosslinking agent in step five.

[0072] Performance testing: Dry cloth breaking strength 90 N; wet cloth breaking strength 48 N; water absorption ratio 25 times; retains 13 times the amount of water after centrifugation at 1000 rpm for 5 min; skin contact time 230 minutes; transparency at 600 nm 95%.

[0073] Example 11 The difference between this embodiment and Embodiment 1 is that the base fabric is spunlace nonwoven fabric (60wt% viscose fiber and 40wt% nylon fiber).

[0074] Performance testing: Dry cloth breaking strength 130 N; wet cloth breaking strength 70 N; water absorption ratio 22 times; retains 13 times the amount of water after centrifugation at 1000 rpm for 5 min; skin contact time 200 minutes; transparency at 600 nm 94%.

[0075] Example 12 The difference between this embodiment and Embodiment 1 is that the base fabric is spunlace nonwoven fabric (80wt% Tencel fiber and 20wt% polypropylene fiber).

[0076] Performance testing: The dry fabric breaking strength of the product obtained in this example is 110 N; the water absorption ratio is 19 times.

[0077] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing. The wet cloth breaking strength was 60 N; after centrifugation at 1000 rpm for 5 min, it could retain 11 times the mass of the dry cloth in water; the skin adhesion time was 230 minutes; and the transparency at 600 nm was 91%.

[0078] The test results of the above embodiments show that for products with a weight ≥ 35 g / m³ 2 According to the test methods in GB / T 3923.1-2013 "Textiles - Tensile Properties of Fabrics", the cross-linked cellulose base fabric (Examples 1-12) has a dry breaking strength ≥ 80 N and a wet breaking strength ≥ 45 N. Compared to the untreated 100% Tencel spunlace nonwoven fabric of Comparative Example 1, which has a water absorption ratio of 7 times, the nonwoven fabric treated by this invention (Examples 1-12) can absorb 15-30 times its weight in water. It has good water retention capacity, retaining 10-15 times its weight in water even after centrifugation at 1000 rpm for 5 min. The base fabric obtained after treatment by this invention is softer after water absorption equilibrium, and the skin-adhesive time is extended by 10-15 times. The transparency at 600 nm is >90%, so the wound healing can be observed without removing the dressing, avoiding secondary damage to the wound surface that may occur during wound examination.

[0079] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a cross-linked cellulose-based dry absorbent fabric, characterized in that, Includes the following steps: (1) The base fabric is soaked in potassium chloride solution, heated, washed, and processed by a rolling mill until the water content is 50wt%-90wt% to obtain sample a; the base fabric, by mass percentage, includes 60%-100% cellulose fiber and 0%-40% non-cellulose fiber. (2) Immerse sample a in sodium hydroxide solution and react to obtain alkalized sample b; (3) Add etherification solution to alkalized sample b, react under microwave assistance, wash, and obtain etherified sample c; wherein the power of microwave assistance is 100-300 W, the reaction temperature is 40-70 ℃, and the time is 2-10 min; (4) Immerse the etherified sample c in the crosslinking agent solution and react at 70-110℃ for 30-120 min. The resulting product is washed and dried to obtain a crosslinked cellulose-based dry absorbent fabric. The solute in the etherification solution in step (3) is at least one of ethylene oxide and chloroacetic acid, and the solvent is at least one of water and ethanol. The mass ratio of solute to solvent is 1-5:20, and the mass ratio of etherification solution to base fabric is 3-10:

1. The solute in the crosslinking agent solution in step (4) is at least one of citric acid and ethylene glycol diglycidyl ether, the solvent is water, the content of the solute in the crosslinking agent solution is 10-40wt%, and the mass ratio of the crosslinking agent solution to the base fabric is 1-10:

1.

2. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The cellulose fiber in step (1) includes at least one of Tencel cellulose, viscose fiber, Modal fiber, cotton fiber, cupro fiber, linen fiber, and acetate fiber; the non-cellulose fiber is an alkali-resistant non-cellulose fiber, including at least one of nylon fiber, vinylon fiber, and polypropylene fiber. The base fabric in step (1) is at least one of spunlace nonwoven fabric, needle-punched nonwoven fabric, sewn nonwoven fabric, knitted fabric, and woven fabric.

3. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: In step (1), the concentration of the potassium chloride solution is 20wt%, the mass ratio of the base fabric to the potassium chloride solution is 1:5-15, the heating temperature is 50℃, the time is 1h, and the pressure of the rolling mill is 0.5 MPa.

4. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: In step (2), the mass ratio of sodium hydroxide to water in the sodium hydroxide solution is 1-10:50, the mass ratio of sodium hydroxide solution to base fabric is 4-16:1, the reaction temperature is 25-60℃, and the reaction time is 30-180min.

5. A cross-linked cellulose-based dry absorbent fabric prepared by the method according to any one of claims 1-4.

6. The application of the cross-linked cellulose-based dry absorbent fabric of claim 5 in wound dressing materials.

Citation Information

Patent Citations

  • High-water-absorption fiber and preparation method thereof

    CN113818232A

  • Preparation method of cellulose fiber-containing gelatinized spunlace non-woven fabric

    CN114645456A

  • Preparation method of skin-friendly composite fiber with high water absorbability

    CN117661325A

  • Polymer hydrogels and methods of preparation thereof

    US20100234233A1